Flame retardant and anti-dripping polyethylene terephthalate fabric based on bio-based phytic acid/gelatine coating - Fang, Yinchun; Wu, Jianguo; Chang, Shuo; Wu, Lingshuang (Surface engineering, 2023)
The application of polyethylene terephthalate (PET) is restricted due to its high flammability and dripping phenomenon. This paper used bio-based phytic acid (PA) and gelatine (G) for flame retardant and anti-dripping treatment of PET fabric. The coated PET fabric achieved a limiting oxygen index (LOI) value greater than 29.5% and no dripping phenomenon revealing that its flame retardancy and anti-dripping properties were obviously improved. The LOI value of PA/G coated PET fabric after washing was over 26% showing good washing durability. The PA/G coating could change the starting decomposition stability and the degradation process of PET fabric and promote to form the stable char. PA/G coating formed an intumescent flame retardant (IFR) system on PET fabric to act through the IFR mechanism. This research is expected to result in a novel eco-friendly coating for flame retardant and anti-dripping thermoplastic polyester fabric.